2020
DOI: 10.1002/ejp.1511
|View full text |Cite
|
Sign up to set email alerts
|

ZNRD1‐AS and RP11‐819C21.1 long non‐coding RNA changes following painful laser stimulation correlate with laser‐evoked potential amplitude and habituation in healthy subjects: A pilot study

Abstract: Background Non‐coding RNAs (lncRNAs) are a group of non‐coding RNAs that act as regulators of gene expression; they are implicated in various human diseases and have been reported to be involved in the modulation of pain. We aimed to study whether: (a) lncRNAs modifications could be found in an experimental model of pain; (b) there was a correlation between lncRNA changes and laser evoked potential (LEP) amplitude/laser‐pain rating. Methods Laser evoked potentials were recorded from 11 healthy subjects to both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
(88 reference statements)
0
6
0
Order By: Relevance
“…It is currently unclear whether the changes caused by experimental muscle pain can be identified only in the alteration in a short time (30 minutes) or the effect could include the changes continuing to develop up to 24 hours after the insult. Even though the alteration of miRNA has not been thoroughly investigated in relation to acute pain, a study has evaluated changes in other circulating non‐coding RNA after laser stimulation showing an alteration of these molecules in the serum of healthy participants (Santoro et al, 2020). A recent study has highlighted how alteration of circulating miR‐1 in acute chest pain improves the diagnosis of acute myocardial infarction (AMI) when evaluated at 3 hours from chest pain onset (Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is currently unclear whether the changes caused by experimental muscle pain can be identified only in the alteration in a short time (30 minutes) or the effect could include the changes continuing to develop up to 24 hours after the insult. Even though the alteration of miRNA has not been thoroughly investigated in relation to acute pain, a study has evaluated changes in other circulating non‐coding RNA after laser stimulation showing an alteration of these molecules in the serum of healthy participants (Santoro et al, 2020). A recent study has highlighted how alteration of circulating miR‐1 in acute chest pain improves the diagnosis of acute myocardial infarction (AMI) when evaluated at 3 hours from chest pain onset (Su et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected at baseline for every participant at 09:00 to avoid normal fluctuations of blood composition molecules. Additional blood samples were collected 30 minutes, 3 hours and 24 hours after the injections, to make sure to avoid a “plateau” effect of the miRNA expressions (Santoro et al, 2020). Samples were not obtained directly after saline injection, to avoid alteration of the pain perception derived from the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Habituation of the N2-P2 amplitude was shown to be affected by a genotype involved in monoaminergic activity and regulators of gene expression. 19,84 Age effects on the N2-P2 amplitude showed an increase in habituation over several groups between 18 and 72, although there were no differences between the groups after a Bonferroni correction. 17 Another study reported a decrease in the N2-P2 amplitude in participants between 50 and 70 compared with young subjects (mean age 5 24.9 years).…”
Section: Population Characteristicsmentioning
confidence: 95%
“…Studies show how lncRNA are involved in several physiological and pathological processes acting in different pathways on several genes at transcriptional, post-transcriptional, and epigenetic levels [31,32]. Moreover, LncRNA have been associated with responses to experimental pain [20,22,[33][34][35] and has been suggested as a new target for future pain therapies [36,37]. Previous studies have been looking deeply at the expression of different RNA and ncRNA in relation to the pathophysiology of OA [38,39].…”
Section: Lncrna Modifications and Pain In Koamentioning
confidence: 99%
“…Moreover, Fu and colleagues showed variable expression of lncRNA in the cartilage of OA patients, demonstrating upregulation of a specific lncRNA, uc.343, that acts on genes implicated in the development of cartilage, leading to a cartilage disruption and faster progression of OA [21]. In a human experimental phasic pain model two lncRNA, such as ZNRD1-AS and RP11-819C21.1, were up-regulated and directly correlated with features of the laser evoked potential suggesting that lncRNA could be involved in abnormal excitability of the cerebral cortex in relation to pain [22].…”
Section: Introductionmentioning
confidence: 96%